Retracted: Multi‐vehicle group‐aware data protection model based on differential privacy for autonomous sensor networks - Jiazheng Yuan; Zhuang Wang; Cheng Xu; Hongtian Li; Songyin Dai; Hongzhe Liu (IET Circuits, Devices and Systems)
Abstract Retraction: [Jiazheng Yuan, Zhuang Wang, Cheng Xu, Hongtian Li, Songyin Dai, Hongzhe Liu, Multi‐vehicle group‐aware data protection model based on differential privacy for autonomous sensor networks, IET Circuits, Devices & Systems 2022 (https://doi.org/10.1049/cds2.12140)].The above article from IET Circuits, Devices & Systems, published online on 29 December 2022 in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the Editor‐in‐Chief, Harry E. Ruda, the Institution of Engineering and Technology (the IET) and John Wiley and Sons Ltd. This article was published as part of a Guest Edited special issue. Following an investigation, the IET and the journal have determined that the article was not reviewed in line with the journal's peer review standards and there is evidence that the peer revie process of the special issue underwent systematic manipulation. Accordingly, we cannot vouch for the integrity or reliability of the content. As such we have taken the decision to retract the article. The authors have been informed of the decision to retract.